An Analysis of Reading Texts in English Textbook Based on Teachers’ Perception - Mona Afersa; Desi Andriani; Rosi Kumala Sari (ITScience (Information Technology and Science), 2022)
This research aims to analyze reading texts in English textbooks based on teachers' perceptions. This research data were the reading texts in the student's English textbook of the 2013 curriculum for grade XI semester I. The Source of the data in this research was divided into two. First is the analysis checklist of reading texts in the students' English textbook of the 2013 curriculum for grade XI semester three analysts filled me. Two analysts are the English teachers at different schools that implement the 2013 curriculum, while the other is the researcher herself. Second is the interview with the teacher, who is also one of the analysts, to get more data about the teacher's perception of the reading texts, especially about the strength and weaknesses of the indicator. After the researcher collected and analyzed two pieces of data, she found in this research that reading texts fulfills the good criteria of reading text in terms of interest, authenticity, cultural background knowledge, text layout, text visuals, and values. On the other hand, the lexical knowledge in the reading text is not suitable for the students' level. There are many unfamiliar words found in each reading text. Then, some of the sentences are included in complex sentences that are not suitable for the students' level, especially for the second grade of senior high school students.